Continuous subcutaneous insulin infusion (CSII) versus multiple daily injections (MDI) of rapid-acting insulin analogues and detemir in type 1 diabetic (T1D) pregnant women. (February 2015) - Mello, Giorgio; Biagioni, Sara; Ottanelli, Serena; Nardini, Camilla; Tredici, Zelinda; Serena, Caterina; Marchi, Laura; Mecacci, Federico
Abstract Objective: To compare glycemic control, maternal-neonatal outcomes and fetal fat body mass growth of type 1 diabetic pregnant women treated with continuous subcutaneous insulin infusion (CSII) or multiple daily injections (MDI) with the long-acting insulin analogue detemir as basal insulin. Methods: Retrospective study of 53 women, attending the Unit of Prenatal Medicine of Careggi University Hospital, Florence, from 2009 to 2012: 35 treated with CSII, 18 with MDI-detemir. Each woman performed daily blood glucose self-monitoring, had an individualized nutritional therapy, weekly prenatal visits and ultrasound scans (US) according to the Tuscan guidelines. US were also performed every two weeks from 28 to 38 weeks of gestation to assess fetal fat body mass growth. Student's t-test and Chi-square test were performed to compare the groups' results. Results: No significant differences were observed in metabolic control, in any maternal and neonatal outcome nor fetal fat body mass growth for either group. The MDI group needed higher daily doses of insulin (MDI: 1.00 ± 0.32 UI/kg versus CSII: 0.75 ± 0.29 UI/kg, p = 0.007) to reach results comparable to the CSII group. Conclusions: MDI therapy with detemir is a safe and effective alternative, with a good benefit–cost ratio compared to insulin pumps.